2020
DOI: 10.3390/agronomy10101535
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Cultivar-Specific Effects on Potato Root and Soil Fungal Diversity

Abstract: The soil fungal community plays an important role in determining plant growth and health. In this study, we investigated the fungal diversity and community composition in the roots and soil of 21 potato (Solanum tuberosum L.) cultivars using high-throughput sequencing at three different time points across the growing season. In soil and roots, the fungal richness and relative abundance of pathogens and saprotrophs were mainly affected by sampling time. While sampling time affected fungal composition in soil, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…The findings showed that under the same soil type and conditions, different RP cultivars induced a shift in soil fungal communities. This is in line with previous reports showing that different cultivars of potato ( Solanum tuberosum L.) and maize had significantly shifted soil fungal diversity and composition [ 55 , 56 ]. For instance, Loit et al [ 55 ] found that among twenty-one potato cultivars, Viviana, Solist, Glorieta, and Concordia significantly affect the overall fungal, pathogen, and saprotrophic community composition.…”
Section: Discussionsupporting
confidence: 93%
“…The findings showed that under the same soil type and conditions, different RP cultivars induced a shift in soil fungal communities. This is in line with previous reports showing that different cultivars of potato ( Solanum tuberosum L.) and maize had significantly shifted soil fungal diversity and composition [ 55 , 56 ]. For instance, Loit et al [ 55 ] found that among twenty-one potato cultivars, Viviana, Solist, Glorieta, and Concordia significantly affect the overall fungal, pathogen, and saprotrophic community composition.…”
Section: Discussionsupporting
confidence: 93%
“…Our research was conducted at one of the University of Wyoming's research and extension facilities, with other potential host crops being grown in the same soils over the past several growing seasons. Having acknowledged this, previous research found a similar phenomenon [25,45], with Fusarium being one of the dominant genera in soils under potato. This suggests that even though our experimental plots may have been enriched due to the planting of successive susceptible crop species, the abundance of Fusarium spp.…”
Section: Discussionmentioning
confidence: 70%
“…The rhizosphere is considered a "hot-spot" for microbial abundance and metabolic activity due to the nutrients released by plant roots (Kuzyakov and Blagodatskaya, 2015). Plant cultivar is a primary factor that determining overall fungal, pathogen and saprotrophic community composition (Loit et al, 2020). Consideration that, root exudates contain released ions i.e., H + , inorganic acids, oxygen and water, but mainly consist of carbon-based compounds.…”
Section: Discussionmentioning
confidence: 99%